2001
DOI: 10.1074/jbc.m008426200
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular Pro-phenoloxidase of the Silkworm, Bombyx mori

Abstract: Pro-phenoloxidase (proPO) in insects is implicated in the defense against microbes and wounding. The presence of proPO in the cuticle was suggested more than 30 years ago, but it has not been purified. The extract of cuticles of the silkworm, Bombyx mori, was shown to contain two proPO isoforms (F-type and S-type proPOs, which have slightly different mobilities in polyacrylamide gel electrophoresis under nondenaturing conditions). The two isoforms were purified to homogeneity. From hemolymph of the same insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 41 publications
7
37
0
Order By: Relevance
“…Moreover, the in vitro PO activity was inhibited by PTU (Fig. 3A), consistent with a previous report (27). We further tested the stimulatory effect of pPG on melanization in vivo.…”
Section: Resultssupporting
confidence: 72%
“…Moreover, the in vitro PO activity was inhibited by PTU (Fig. 3A), consistent with a previous report (27). We further tested the stimulatory effect of pPG on melanization in vivo.…”
Section: Resultssupporting
confidence: 72%
“…This is similar to the enzymes from the haemocytes of Penaeus californiensis and Pacifastacus leniusculus, and from the egg masses of Biomphalaria glabrata [22,47,49]. Fig.…”
Section: Discussionsupporting
confidence: 72%
“…In A. subalbatus at least five distinct PPOs have been identified and the genomes of Drosophila melanogaster and Manduca sexta have three PO genes. However, only two cDNAs encoding PPOs have been reported in most of other lepidopteran insects, for example Hyphantria cunea (Park et al 1997), B. mori (Asano and Ashida 2001), H. virescens (Shelby and Popham 2008) and C. fumiferana (Doucet et al 2008). In our study, by using native-PAGE and coloration with standard substrate L-dopa, we found that P. xylostella also has two PPO isoenzymes, PxPPO1 and PxPPO2, which was further proved by sequencing of their cDNA.…”
Section: Discussionsupporting
confidence: 58%